Mapping of Ecosystem Services of Land Cover and Geomorphology in Water Provision in Bali Province for 2018 and 2024 - Ni Luh Putu Intan Sintya Dewi; Ni Made Utami Dwipayanti; I Gede Mahardika (PT Publikasiku Academic Solution, 2025)
High number for water demand in Bali always increasing while the ability is limited in environment. this condition influence by land conversion, pollution, and climate change impact. This condition has led to a projection that Bali will experience a clean water shortage starting in 2025. This study aims to map and analyze the index of water supply ecosystem services in Bali Province as an effort to maintain environmental carrying capacity. The research method used is ecosystem service mapping with an ecosystem service index calculation based on land cover and geomorphology proxies. Data were obtained from an assessment by seven experts using the Analytical Hierarchy Process (AHP) and pairwise comparison methods. Secondary data, in the form of land cover and geomorphology maps of Bali from 2018 and 2024, were used as the main spatial data. The results show that land use change has a significant impact on the water supply ecosystem service index in Bali. The ecosystem service index for land cover in Bali is categorized as low, while the ecosystem service index for geomorphology (original landforms) is categorized as moderate. Further analysis indicates that the area of rice fields and primary dry land forests has decreased from 2018 to 2024. Meanwhile, volcanic land, which dominates the Bali region, has a moderate capacity for water supply. The conclusion of this study is that the water supply ecosystem service index in Bali Province still needs to be improved.